AUGUSTE COMTE’S POSITIVISM: THE IDEA OF VALUE-FREE SCIENCE IN POSITIVISM ACCORDING TO THE ISLAMIC VIEW AND IT’S IMPLICATIONS FOR ISLAMIC EDUCATION - Okta Anuhgra, Yudha (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
Islamic education encompasses not only worship but included in it is the aspect of using reason to understand God's creation and how the universe works. Science continues to develop and requires humans to be able to adapt to developments over time. Comte's positivist thinking can be linked to the context of Islamic education in giving rise to efforts to strengthen Islamic education. This research explores Auguste Comte's positivist thinking, compares it with Islamic values, and examines the potential of positivism for Islamic education. This research explores Auguste Comte’s positivism, contrasting it with Islamic values, and examines the potential of positivism for Islamic education. This research uses a qualitative approach, utilizing literature reviews from various relevant books and journals. This research ultimately produced findings that Comte’s positivism elevates the scientific method while sidelining metaphysical discussions, including religion. Key characteristics of positivism are value-free perspectives, phenomenalism, reductionism, naturalism, and mechanism. Comte proposed a “law of three stages” outlining human development from theological to metaphysical and finally to positivistic stages. While he did not advocate abandoning religion, he sought to separate science and religion. Comte's view of trying to separate science from religion is contrary to Islam's emphasis on religious values. Islamic education can adopt aspects of positivism by enhancing empirical and interdisciplinary studies. Also, prioritizing scientific and empirical inquiry in understanding phenomena to foster critical thinking and innovation within an Islamic education framework. Thus, integrating empirical, interdisciplinary, and scientific studies within Islamic education can enrich itself while maintaining its foundational values.